Neslovnični kvalifikatorji in kvalifikatorska pojasnila v zgodovinskem slovaropisju - Legan Ravnikar, Andreja (Slavia Centralis, 2020)
Non-grammar qualifiers and qualification explanations in historical lexicographySlovar slovenskega knjižnega jezika 16. stoletja (SSKJ16) is an explanatory historical dictionary with elements of a translation and encyclopaedic dictionary. The explanations of lexemes’ meanings are clarified by non-grammar qualifiers (indicators) and non-grammar qualifying explanations; much like in the case of modern normative-explanation dictionaries, the qualifiers in historical dictionaries include common meaning-, expressive, social-, terminological and frequency qualifiers. A speciality is the so-called certainty qualifier (uncertain), which indicates in rare cases the uncertain definition of an entry’s meaning. Qualifying explanations are rather common in the SSKJ16, requiring classification into several groups.
Keywords: historical lexicography; Slovar slovenskega knjižnega jezika 16. stoletja; non-grammar qualifiers; non-grammar qualifying explanations